Trade-offs and synergistic evolution of ecosystem services and land use driving mechanisms in karst ecologically vulnerable areas of China - Dan Zhang; Zhongfa Zhou; Lu Zhang; Quan Chen; Dan Luo; Denghong Huang; Qing Feng; Changli Zhu (Geocarto International)
The trade-offs and synergies of ecosystem services (ES) in karst fragile ecosystems are vital for regional sustainability. This study quantifies soil retention (SR), water supply (WS), and carbon storage (CS) in the Nanpan and Beipan River Basin (1985-2020). ES hotspots/coldspots were identified via Getis-Ord Gi* analysis; bivariate Moran's I revealed interaction patterns. Land use transitions impacting ES interactions were assessed through transition matrices combined with spatial overlays.The results show: (1) SR and WS increased significantly, while CS rose marginally. Spatially, ES capacity was higher in the north; hotspots clustered in forests/grasslands contrasted with coldspots in cropland/urban areas. (2) ES interrelationships were predominantly synergistic. High-synergy areas clustered in densely vegetated zones, contrasting with urbanized low-synergy/trade-off areas. (3) High-synergy zones were forest-dominated (mean: 79.18%), contrasting with low-synergy zones (mean forest: 26.40%; grassland: 36.57%) exhibiting extensive cropland conversion. ES synergies were enhanced through optimized land use restructuring via increased forest/grassland coverage from ecological projects.